The association between newborn screening analytes as measured on a second screen and childhood autism in a Texas Medicaid population. Issue 6 (13th July 2020) - Langlois, Peter H.; Canfield, Mark A.; Rutenberg, Gary W.; Mandell, Dorothy J.; Hua, Fei; Reilly, Brendan; Ruktanonchai, Duke J.; Jackson, Janice F.; Hunt, Patricia; Freedenberg, Debra; Lee, Rachel; Villanacci, John F.
Abstract: Autism (or autism spectrum disorder [ASD]) is an often disabling childhood neurologic condition of mostly unknown cause. We previously explored whether there was an association of ASD with any analyte measured in the first newborn screening blood test. Here we explore the second screen. Our matched case–control study examined data on 3–5 year‐old patients with any ASD diagnosis in the Texas Medicaid system in 2010–2012. Subjects were linked to their 2007–2009 newborn screening blood test data, which included values for 36 analytes or analyte ratios. Data were available for 3, 005 cases and 6, 212 controls. The most compelling associations were evident for fatty acid oxidation analytes octanoylcarnitine (C8) and octanoylcarnitine/acetylcarnitine (C8/C2). Their adjusted odds ratios comparing 10th versus first analyte deciles were between 1.42 and 1.54 in total births, term births, and males. C8 was consistent with first screen results. Adipylcarnitine (C6DC), an organic acid analyte, showed opposite results in the two screens. Several other analytes exhibiting significant associations in the first screen did not in the second. Our results provide evidence that abnormal newborn blood levels of some carnitines may be associated with risk of later ASD, possibly related to their involvement with mitochondrial function in the developing brain.